2014
DOI: 10.18632/oncotarget.2321
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 signaling contributes to cell growth, anti-apoptosis and metastasis in salivary adenoid cystic carcinoma

Abstract: Background: Numerous studies have reported both the tumor-suppressive and oncogenic roles of the Notch pathway, indicating that Notch activity regulates tumor biology in a complex, context-dependent manner. The aim of the present study was to identify the role of NOTCH1 in the cell growth and metastasis of SACC.Methods: We analyzed the expression of NOTCH1 in clinical SACC samples using immunohistochemical staining. We silenced the expression of NOTCH1 and overexpressed activated NOTCH1 to elucidate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…The role of NOTCH in carcinogenesis has been explored in a mouse model in which an activated NOTCH4 transgene induces neoplastic transformation of mammary and all three major salivary glands . Overexpression of NOTCH1 in ACC has been recently described and associated with cancer progression . Finally, NOTCH1‐activating mutations recently reported in high‐grade ACC specimens support NOTCH1 as a driver of aggressiveness in ACC.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The role of NOTCH in carcinogenesis has been explored in a mouse model in which an activated NOTCH4 transgene induces neoplastic transformation of mammary and all three major salivary glands . Overexpression of NOTCH1 in ACC has been recently described and associated with cancer progression . Finally, NOTCH1‐activating mutations recently reported in high‐grade ACC specimens support NOTCH1 as a driver of aggressiveness in ACC.…”
Section: Resultsmentioning
confidence: 60%
“…130 Overexpression of NOTCH1 in ACC has been recently described and associated with cancer progression. 131 Finally, NOTCH1-activating mutations recently reported in highgrade ACC specimens 71,83 support NOTCH1 as a driver of aggressiveness in ACC. Similar activating mutations in NOTCH1-3 occur in basal-like breast cancer, 132,133 for which NOTCH1 activation is also implicated in breast cancer progression, chemotherapy resistance, and stimulation of breast CSCs.…”
Section: Sox10mentioning
confidence: 92%
“…A number of studies have confirmed that Notch1 is mainly upregulated in the brain (44), gastric cancer (45), colorectal cancer, leukemia, ovarian cancer and HCC (29). In contrast, Notch1 has also been shown to be downregulated in lung (46), breast (47), prostate, kidney cancer and myeloma (48). It has been shown that Notch1 is involved in tumor cell invasion in pancreatic, breast cancer, lingual squamous cell carcinoma and HCC (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Notch receptor-ligand interaction occurs between two adjacent cells. Notch proteins are synthesized as precursors in the endoplasmic reticulum, and then the Notch intracellular domain (NICD) is released, translocating to the nucleus, driving the expression of HEY1, HES1, Myc, CCND1, Bcl-2 and other cellular process-regulating genes involved in proliferation, differentiation, stem cell maintenance and apoptosis (5).…”
Section: Introductionmentioning
confidence: 99%